Molecular basis of the key regulator WRINKLED1 in plant oil biosynthesis - Qiao, Zhu (2022)
Vegetable oils are not only major components of human diet but also vital for industrial applications. WRINKLED1 (WRI1) is a pivotal transcription factor governing plant oil biosynthesis, but the underlying DNA-binding mechanism remains incompletely understood. Here, we resolved the structure of Arabidopsis WRI1 (AtWRI1) with its cognate double-stranded DNA (dsDNA), revealing two antiparallel β sheets in the tandem AP2 domains that intercalate into the adjacent major grooves of dsDNA to determine the sequence recognition specificity. We showed that AtWRI1 represented a previously unidentified structural fold and DNA-binding mode. Mutations of the key residues interacting with DNA element affected its binding affinity and oil biosynthesis when these variants were transiently expressed in tobacco leaves. Seed oil content was enhanced in stable transgenic wri1-1 expressing an AtWRI1 variant (W74R). Together, our findings offer a structural basis explaining WRI1 recognition and binding of DNA and suggest an alternative strategy to increase oil yield in crops through WRI1 bioengineering.